Microscopic origin of the 1.3 G0 conductance observed in oxygen-doped silver quantum point contacts - SANVITO, STEFANO (My University, 2014)
Besides the peak at one conductance quantum, G0, two additional features at ∼0.4 G0 and ∼1.3 G0 have been observed in the conductance histograms of silver quantum point contacts at room temperature in ambient conditions. In order to understand such feature, here we investigate the electronic transport and mechanical properties of clean and oxygen-doped silver atomic contacts by employing the non-equilibrium Green's function formalism combined with density functional theory. Our calculations show that, unlike clean Ag single-atom contacts showing a conductance of 1 G0, the low-bias conductance of oxygen-doped Ag atomic contacts depends on the number of oxygen impurities and their binding configuration. When one oxygen atom binds to an Ag monatomic chain sandwiched between two Ag electrodes, the low-bias conductance of the junction always decreases. In contrast, when the number of oxygen impurities is two and the O-O axis is perpendicular to the Ag-Ag axis, the transmission coefficients at the Fermi level are, respectively, calculated to be 1.44 for the junction with Ag(111) electrodes and 1.24 for that with Ag(100) electrodes, both in good agreement with the measured value of ∼1.3 G0. The calculated rupture force (1.60 nN for the junction with Ag(111) electrodes) is also consistent with the experimental value (1.66 ± 0.09 nN), confirming that the measured ∼1.3 G0 conductance should originate from Ag single-atom contacts doped with two oxygen atoms in a perpendicular configuration.
PUBLISHED
Keywords: Transmission coefficient; Chemical bonds; Fermi levels; Electrodes; Silver; Nanoscience & Materials